KETENTUAN PENGATURAN KAWIN KONTRAK DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Sukindar, Sukindar (Universitas 17 Agustus 1945 Samarinda, 2020)
Contract marriages are one of the 3 types of marriages known in Indonesia. As it is known that contract marriages are marriages made by certain parties with specific aims and objectives and within a certain period of time. So the marriage is actually a marriage that is not appropriate and deviates from the noble purpose of the actual marriage, which is to form an eternal household and only seek the pleasure of God, in accordance with the provisions as regulated in applicable laws in Indonesia.Therefore, the purpose of this paper is to find out the actual arrangements related to the practice of contract marriages which are still widely practiced in Indonesia.This type of research used in this study is normative juridical type of research, namely research conducted based on the legal scientific character of the normative side.The results of the study showed that the practice of contract marriages that were carried out was not appropriate and violated the provisions of the legislation that acted as positive law in Indonesia. This is due to the contract marriage there are several things that were promised such as, a number of assets that must be issued and the deadline for the end of the marriage has been determined, then obviously such a marriage is a marriage arranged by the parties themselves and ignores the provisions of the applicable laws and regulations. While the regulations that specifically regulate contract marriages have not yet existed in Indonesia.